غصہ میں دی جانے والی طلاق کی شرعی حیثیت ؛ مفتی غلام سرور کے موقف کا تحقیقی جائزہ: ISLAMIC LEGAL STATUS OF DIVORCE IN ANGER: A RESEARCH STUDY OF MUFTI GHULAM SARWAR QADRI'S STANCE (Al-Aasar, 2026)
In recent times, a tremendous increase in divorce rates has been observed in Pakistan as well as across the Muslim world, with domestic issues and intense anger being identified as the primary causes. This situation is severely affecting our family system. Consequently, determining the Islamic legal status of divorce pronounced in a state of intense anger has become an important jurisprudential issue. The primary objective of this article is to clarify the specific stance of Mufti Ghulam Sarwar Qadri on this matter and to present an analytical study of the arguments provided by him. His position states that a divorce pronounced in a state of extreme anger, where a person completely loses his senses, does not take effect. This research substantiates this viewpoint using various scholarly and jurisprudential arguments. The article utilizes Quranic verses, Ahadith, and authoritative texts of Hanafi jurisprudence. The fundamental outcome of this study is to raise awareness within the Muslim Ummah regarding the different states of anger, thereby minimizing the negative impact of this sensitive issue on the family system.